Extratos de Hesperozygis ringens (Benth.) Epling como antibacterianos em piscicultura - Rosa, Isadora Aguirre (2019)
Aquaculture is constantly expanding in our country and worldwide. Concomitant to this growth, the occurrence of bacterioses related to stressful situations to which fish are constantly subjected, such as the high population density in nurseries, poor water quality and inadequate management conditions, has been increased, resulting in high mortality rates and damage to fish farmers. The bacterium Aeromonas hydrophila is one of the main pathogens in aquaculture, especially affecting the jundiá (Rhamdia quelen). Natural products characterize an alternative source for the treatment and/or prevention of diseases in veterinary medicine, in view of the various advantages they present compared to products of synthetic origin. The species Hesperozygis ringens (Benth.) Epling (Lamiaceae), popularly known as "espanta-pulga", deserves special mention, since its essential oil has properties applicable to aquaculture, such as larvicide, antimicrobial, antiparasitic and anesthetic. For this reason, this study aimed to evaluate the potential of extracts of H. ringens as antibacterial in fish farming. For this, the leaves were collected, dried, ground and extracted sequentially with hexane and, later, ethanol, in Soxhlet apparatus. The concentrated extracts were kept in desiccator and lyophilized. The in vitro antibacterial activity of the extracts was evaluated by the broth microdilution method. The hexane extract of H. ringens (HEHR) showed the best result in the in vitro assays and was used for the in vivo survival assay, where jundiá juveniles experimentally infected with A. hydrophila were exposed to a single therapeutic bath containing the different treatments (HEHR at 15 and 30 mg/L; 4 mg/L florfenicol). Mortality was assessed for 7 days. For the identification of the phytochemicals present in the volatile fraction of the HEHR, gas chromatography coupled to mass spectrometry was used, for quantification of the same, gas chromatography with flame ionization detector. The HEHR was effective in in vitro susceptibility assays with weak antibacterial activity (minimal inhibitory concentrations, MICs, and minimal bactericidal, MBCs, between 1600 and 6400 μg/mL) against A. hydrophila, Aeromonas veronii, Citrobacter freundii and Raoultella ornithinolytica. Six phytochemical constituents were identified in the volatile fraction of the HEHR, and the monoterpenoid pulegone was characterized as the majority. This extract allowed a relative survival rate of 93.33% of jundiás experimentally infected by A. hydrophila 7 days after a single therapeutic bath at 30 mg/L, whereas the antimicrobial florfenicol, promoted a rate of 60%. EHHR is a promising biodegradable source for the control and treatment of bacterial infections in organic aquaculture.